Kaizen Costing sebagai Perbaikan Berkelanjutan untuk Meningkatkan Keunggulan Bersaing pada E-Commerce - Sahri, Nurlaeli Aprilia; Novita, Novita (Universitas Swadaya Gunung Jati, 2019)
This study aims to analyze the application of kaizen costing as a continuous improvement to improve the competitive advantage of e-commerce. Kaizen is widely applied to Japanese companies with the concepts of 3M (Muda, Mura, Muri) and 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) that can help management in managing workplaces, improve employee discipline, reduce waste, improve company quality and efficiency . E-commerce as the object of research is PT Aplikasi Karya Anak Bangsa (Go-Jek Indonesia) which involves employees, drivers, and customers as research samples. The method of data collection is done through observation, documentation, interviews and questionnaires. Methods of data analysis through descriptive analysis and verification using the Partial Least Square (PLS) program. Based on the survey results, respondents' responses and company conditions concluded that Go-Jek had implemented the kaizen costing concept in the face of e-commerce competition. However, only the variables Muri, Seiso, Seiketsu, Shitsuke which only have a significant effect on the variable of competitive advantage. This is because the number of respondents who have not felt the effectiveness of the company in implementing kaizen costing.Keywords: Kaizen costing; Continuous improvement; 3M; 5S; Competitive advantage